Contraceptive practice and commodity sources amongst female undergraduates in Ibadan, Southwest Nigeria (2008)
Objective: To determine the pattern of contraceptive use, and its sources among female undergraduates of the University of Ibadan. Methodology: A cross-sectional study design using self administered questionnaire. The study was conducted from November 2005 till March 2006. Results: The result of one thousand six hundred and thirty respondents were analysed out of 1800 interviewed. The commonest age group was 21-25years and about half were in their second and third undergraduate training year. They were mostly single, Christians and of the Yoruba ethnic group. Among those interviewed, 84% admitted to previous sexual activity. However, only a third had ever used any form of modern contraception. The commonest method of contraception ever used was male condom (82.0%) and the least was implantable contraception (1.4%). Other methods used included spermicides, oral contraceptive pills, and injectables. Of those that used contraception, 59.0% procured the service/commodity from pharmacy shops and patent medicine outlet. Other sources mentioned included; non-governmental organization private hospitals, and friends/relatives. Some did not indicate the source of procurement. Conclusion: The study revealed that students in Nigeria engage in risky sexual practices which may be detrimental to the future reproductive activities. Even those that claim to use contraceptives may not have been properly counseled prior to use. We recommend that safer sexual practices should be encouraged and some emphasis on abstinence. Advocacy on appropriate sources of contraceptives commodities should be pursued